Diabetic Macular Edema: Traditional and Novel Treatment - Martina Tomić; Romano Vrabec; Tamara Poljičanin; Spomenka Ljubić; Lea Duvnjak (Acta Clinica Croatica, 2017)
Diabetes is one of the leading public health problems worldwide. Diabetic macular edema (DME) is the main cause of vision loss in patients with diabetes. Ideal metabolic control of diabetes is the primary goal of treatment and the basic way of preventing and stopping the progression of DME. Although laser photocoagulation has been the standard treatment of DME for nearly three decades, superior outcomes can be achieved with novel, intravitreal anti-VEGF and steroid therapy. Novel treatment option for DME depends on visual acuity and location/extent of macular thickening based on optical coherence tomography scans. According to the International Clinical Classification Scale, DME is divided into no center-involving DME and center-involving DME (CI-DME). New guidelines recommend intravitreal treatment as the treatment of choice for patients with CI-DME and moderate visual impairment. Patients with no CI-DME and mild visual impairment should be treated with modified ETDRS laser photocoagulation and closely observed. Vitrectomy is the treatment of choice for patients with a tractional component of DME. Nowadays, traditional treatment goal of preventing blindness in patients with DME has been changed by the new goal aiming to restore impaired vision, prevent further vision loss and improve visual function. Therefore, many trials addressing this new concept have been underway worldwide.